Proposed Growth Strategy For Dian Institutepare - Maulana, Danis; Toha, Mohammad (The Indonesian Journal of Business Administration, 2014)
Abstract- The growth of formal education and non-formal education is very promising in Pare, the number of competitor in education institution is also increasing. The competition is getting tougher, requires every education learning doing innovation, development and improvement in their course program to get new target market. In order to overcome the competition, Dian Institute should know what positioning strategy could be used for prospective students especially for new target market The strategy formulation begins with analyzing external and internal environment to identify opportunities and threats of the industry as well as the strengths and weaknesses of the company using several methods such as Political, Legal, Socio-Cultural and Technology (PEST) Analysis, Porter’s Five Forces Analysis, Competitor Analysis, Current Business Model Analysis, and Value Chain Analysis. The SWOT derived from the external and internal analysis is then used to generate IFAS and EFAS score, and interpreted to the Grand Strategy Selection Matrix and Four basic strategic, determining the current position of the Dian Institute and the strategy it should execute. The result of the analysis indicates Dian Institute in quadrant 1 of grand strategy. Quadrant I of the Grand Strategy Matrix are in an excellent strategic position. For Dian Institute, continued concentration on current markets (market penetration and market development) and products (product development) are appropriate strategies.so that after succeeding in growth strategy, author make new business model canvas for Dian Institute for make this business better .All things considered, to analyze the current business situations and internal conditions of Dian Institute as the basis of strategies formulation. And to develop growth strategies that can be implemented by Dian Institute to get new target market and the last one to design the implementation plans of the growth strategy that can be conducted by Dian Institute which is adjusted with institution competition in pare market. Keywords: growth strategy, Business model, service industry, Strategic positing